Compassion Fatigue and Coping Skills of Philippine National Police First Responders in Bacolod City - Miguel R. Lim; Jasmin L. Parreño (Philippine Social Science Journal, 2020)
Enforcing the law to maintain peace, justice, and order in the community involves the police first responder in situations that are traumatic and cause negative health outcomes. Police are tasked with maintaining peace and helping traumatized victims. Over time, the struggle to alleviate the victims' suffering may come with a cost. Compassion fatigue has multiple negative effects on police well-being and occupational performance. Compassion fatigue refers to the physical and mental fatigue and emotional withdrawal encountered by those who attend for sick or traumatized people over a lengthened period. In contrast, coping skills means investing one's own intentional effort to resolve personal and interpersonal difficulties in order to try to comprehend, reduce, or permit compassion fatigue. The paper describes the extent of compassion fatigue and coping skills of the PNP first responders in Bacolod city. Likewise, it explores the relationship between the Philippine National Police (PNP) first responder's demographics and their compassion fatigue and coping skills. Also, it determines the correlation between compassion fatigue and coping skills of PNP first responders.